2021
DOI: 10.1186/s40649-021-00092-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analyzing users’ behavioral strategies with co-evolutionary process

Abstract: Social networking services (SNSs) are constantly used by a large number of people with various motivations and intentions depending on their social relationships and purposes, and thus, resulting in diverse strategies of posting/consuming content on SNSs. Therefore, it is important to understand the differences of the individual strategies depending on their network locations and surroundings. For this purpose, by using a game-theoretical model of users called agents and proposing a co-evolutionary algorithm c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We believe that agents' appropriate strategies differ depending on their local situation, such as the number of connections (i.e., friends and/or followers) and neighbors' strategies determine utility maximization. Miura et al [22] proposed MWGA, in which agents in an SNS-NG co-evolve diverse strategies [32]. Subsequently, Ueki et al [13] applied MWGA to SNS-NG/MQ.…”
Section: Multiple-world Gamentioning
confidence: 99%
“…We believe that agents' appropriate strategies differ depending on their local situation, such as the number of connections (i.e., friends and/or followers) and neighbors' strategies determine utility maximization. Miura et al [22] proposed MWGA, in which agents in an SNS-NG co-evolve diverse strategies [32]. Subsequently, Ueki et al [13] applied MWGA to SNS-NG/MQ.…”
Section: Multiple-world Gamentioning
confidence: 99%
“…Literature [11] put forward the concept of Omni channel retailer sales model and analysed the impact of Omni channel strategy on product demand, channel strategy, and member profit. Literature [12] studied the impact of consumers' channel migration behavior on retailers' revenue through the channel strategy of "online purchase and offline pick-up." Literature [13] research showed that when there are great differences in products from different channels, retail enterprises can increase their own income by choosing the coexistence of online and offline sales.…”
Section: Introductionmentioning
confidence: 99%